SISTEM INFORMASI MANAJEMEN LOMBA BURUNG BERKICAU DI BNR POTRE KONENG PAMEKASAN - Siti Hozayna (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
Boy N Rusly (BNR) Pamekasan is a chirping lover community in Pamekasan district. Nowadays, there are many bird enthusiasts in various regions. Bird enthusiasts find it difficult to find information about bird race schedules. Participants find it difficult to get information to register and see the value of the results of the race. Similar to the registration payment that can be done during registration or after the competition, this sometimes causes incompatibility of registration data with the money obtained because there are participants who have not paid the registration fee. Of the various problems experienced by bird enthusiasts and the bird race committee, we need a technology that is globalized so that it can be accessed at any time. One solution to overcome this problem is that an Android-based bird contest application is needed so that it can be used by bird fans and the bird race committee to solve this problem and make it easier for participants to get information, purchase ticket processes and view the results of the competition assessment. Making management information system Twitter birds contest to be easily accessed by websites and smartphones, so for the design and development of mobile and website-based applications. Data collection was carried out by observation, literature study and interviews. Then the data is applied to the website and smartphone application. To implement website and mobile based applications designed with the Java programming language and Codeigneter. System testing uses the waterfall method to test sequentially.